Tectonic Geomorphology Between Thakot and Mansehra, Northern Pakistan - Lawrence, Robert D.; Shroder Jr., John F. (Journal of Himalayan Earth Sciences, 1985)
Geomorphic features between Thakot and Mansehra include (1) bedrock terraces and an associated knickpoint on Nundihar Khwnr, an Indus tributary, (2) deeply weathered residual soils on n relict upland surface called the Chattar plain, (3) an escarpment developed at the edge of headward erosion into this upland surface, and (4) an incised intermontane sedimentary basin north of Mansehra. Together these features provide new data to be used in reconstructing the history of recent ublift of the Himalaya in Pakistan. They reflect a period of relative tectonic stability during tropical soil development on a surface of rolling hills between about 25 and 5 m.y .ago followed by uplift and erosion of that surface. These residual soils may be an important sediment source for the voung intermontane basins developed in association with foreland thrust fault motion during the last 5 m.y.